Особливості врахування граничних періодів прогнозування на базі динамічної моделі математичного програмування розвитку генеруючих потужностей атомної енергетики - Shulzhenko S.V. (General Energy Institute of the National Academy of Sciences of Ukraine, 2015)
A mathematic optimization model with integer-valued variable for the development of the national atomic energy sector is suggested. The model is capable of accounting limit forecasting periods, constraints on available investment resources, time lag required for installing generation capacities, and their service life. It is implemented based on the MathProg modeling language, which enables developing and implementing mathematical programming models focused on addressing tasks of certain class such as development of the national power engineering sector, rather than some individual tasks. Specific implementation of the model could be carried out by adjusting input data only. Having regard to the speed at which the presented model with integer-valued variable comes up with solutions (0.2 sec), a conclusion can be made about the prospects of using GLPK packages for the search of optimal solutions regarding more complex energy sector development models.